Characterization of MEMS comb capacitor - Ahmad, F. (Springer, 2020)
With the advancement of micro-electro-mechanical systems (MEMS) technologies, it is compulsory to have the sources which power the micro devices at micron scale. Due to the miniaturization, compactness, inexpensive and ease of integration with the standard process compatibility, CMOS-MEMS capacitor is characterized. There are two major parts of characterization; static mode and dynamic mode. The moveable shuttle remains in static mode until the input voltage reaches to 50Â V. In static mode, due to constant capacitance among stator and shuttle fingers, charge accumulates up to 1.17 pC and level of energy stored does not go so high. The shuttle fingers initially overlap with the stator fingers by 30Â Î¼m but in dynamic mode when the voltage raises above 50Â V, moveable shuttle starts moving and fingers overlapping distance reaches to 50Â Î¼m with the increase in voltage of approximately 307Â V. In dynamic mode, stored energy level increases from 30 to 1800 pJ. The stored energy increases exponentially in dynamic mode due to the increased overlapping of the fingers and against elastic forces of beams (1, 2, 3 and 4). Â© 2019, Springer-Verlag GmbH Germany, part of Springer Nature.